Understanding lithium-ion battery management systems in electric vehicles: Environmental and health impacts, comparative study, and future trends: A review - R. Suganya; L.M.I. Leo Joseph; Sreedhar Kollem (Results in Engineering)
The future of transportation is moving toward electric vehicles (EVs), driven by the global demand for sustainability. At the core of EV technology is the Battery Management System (BMS), which plays a vital role in ensuring the safety, efficiency, and longevity of batteries. Lithium-ion batteries (LIBs) are key to EV performance, and ongoing advances are enhancing their durability and adaptability to variations in temperature, voltage, and other internal parameters. This review aims to support researchers and academics by providing a deeper understanding of the environmental and health impact of EVs. Additionally, the article offers a comprehensive analysis of various algorithms used for parameter estimation in BMS, discussing their advantages, limitations, and practical implications. It also addresses key challenges in EV adoption, such as range anxiety and the development of charging infrastructure. By exploring these aspects, the review provides valuable information on improving BMS efficiency and battery technologies, supporting the future growth of cleaner and more sustainable electric transportation.